A natureza da norma fundamental e sua função na constituição do objeto de uma ciência jurídica pura na segunda edição (1960) da Teoria Pura do Direito - Caruso, Basilio Teodoro Rodrigues (2015)
We intent to demonstrate the function of the fundamental norm on the constitution of the object of legal science, in the context of a Pure Theory of Law, function that give an evidence of it´s nature: the fundamental norm´s nature is similar to transcendental category of Kant´s transcendental idealism. The fundamental norm, as it has been conceived on the second edition of Pure Theory of Law, determines itself as a logic-transcendental condition of an particular conception of law: a juridical conception that, if it´s not a necessary conception, is the only that perform a purity. The fundamental norm, as a transcendental condition of cognoscibility, acts in order to constitute the object Law, what means that the object of legal science is conceived as a juridically pure object, if the fundamental norm is considered as a condition to instauration of the fundamental fact of juridical creation. We pretend to conclude that an analogical relation with the transcendental categories, such it has been conceived by Kant´s idealism, can characterize the fundamental norm as an epistemological condition of this particular conception of law, because fundamental norm is transcendental. However, this relation of analogy grows week because this juridically pure conception is not a necessary, but just a possible conception of law